KEEFEKTIFAN KALIMAT TEKS LAPORAN HASIL OBERVASI SISWA KELAS X SMA NEGERI 3 PADANG PANJANG - Fatimah, Fatimah; Gani, Erizal; Hafrison, Mohammad (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACT The purpose of the study is to describe the effectiveness the text of the observation report of the students at SMA Negeri 3 Padang Panjang.This research is qualitative research with descriptive method.The result in this research shows that the effectiveness of the text of the observation report of students can be said good, 74% of 312 sentences.Based on the results of research, it was concluded six things: (1) the student is still having an error in standard word, (2) still found an error regarding the completeness of the elements, (3) still found a sentence that is not solid, (4) still found errors in the firmness of the sentence, (5) still found waste of words, (6) still found errors about parallelism. Kata kunci: Keefektifan kalimat, laporan hasil observasi